GEOPHYSICAL PROSPECTING ON COAL DEPOSIT AT PARAMBAHAN AREA,WEST SUMATERA - MAMAN SURACHMAN (Indonesian Mining Journal, 2006)
Changing coal mine method from open to underground mines needs preparing new data such as the type and the thickness of rocks as overburden on coal seam. Geophysical prospecting method is chosen to gather such the data. Based on 30 point measurements and compilated by regional geologi- cal data, it was assumed that the rocks at Parambahan area contained top soil, alternating beds of sand, silt and weathered clay, alternating beds of sand, silt and massive clay, coally clay and massive sand stone.